Perovskite‐type Li‐ion solid electrolytes: a review - Lu, Jiayao; Li, Ying (Journal of materials science. Materials in electronics, 2021)
All-solid-state lithium batteries with inorganic solid electrolytes are recognized as the next-generation battery systems due to their high safety and energy density. To realize the practical applications of all-solid-state lithium battery, it is essential to develop solid electrolytes which exhibit high Li-ion conductivity, low electron conductivity, wide electrochemical window, and low interface resistance between the electrode and the solid electrolyte. Among many solid electrolytes, the perovskite-type lithium-ion solid electrolytes are promising candidates that can be applied to all-solid-state lithium batteries. However, the perovskite-type solid electrolytes still suffer from several significant problems, such as poor stability against lithium metal, high interface resistance, etc. In this review, we have analyzed and summarized the properties of perovskite-type solid electrolytes with two different systems, namely three-component oxide system Li 3x La 2/3−x TiO 3 (LLTO) and four-component oxide system (Li, Sr)(B, B’)O 3 (B = Zr, Hf, Ti, Sn, Ga, etc., B’ = Nb, Ta, etc.). LLTO and (Li, Sr)(B, Ta)O 3 compounds exhibit high Li-ion conductivity of up to > 10 − 4 S·cm − 1 at room temperature. Based on the review of academic literature, the ion transportation mechanism, composition design, electrical properties, stability, doping, and application of these solid electrolytes are discussed, which would be helpful for the further development of all-solid-state lithium batteries.